Sketches of Urbanness - Corrente, Michael (InTensions, 2009)
Established property lines in an urban context divide spaces for social human interaction. By having minimal property setback requirements for developers to follow, urban planners have initiated an environment where the interface between building façade and building user offers very little in terms of public social opportunities. Building developers tend to push a formula that requires the building envelope to maximize square footage so that the investor(s) can obtain maximum profit. In doing so, opportunities for social exchange are forced to the public right of way such as the sidewalk or street. In the images that I have created, I am looking to examine sketches of Urbanness. My inquiry is similar to Peter Hamilton’s examination of Post World War II French documentary photographers as they searched for a contemporary sense of ‘Frenchness.’ (Hamilton). Drawing on Hamilton’s reading of the works of the French photo-documentarians, ‘Sketches of Urbanness’ begins to explore the “juxtaposition of the archaic and the modern, the human and the inanimate, glancingly encountered each day in the streets of the modern city.” (Hamilton 114) However, I am not proposing that I am “documenting,” as was the objective of the French photographers studied by Hamilton. Instead, I am using my artwork as a ‘sketchbook,’ one where I am attempting to make visible a sense of Urbanness that recasts the possibilities for public social opportunities in spaces developed with private interests foremost in mind, and is the outcome of my embodied engagement with those spaces. I construct this Urbanness by re-producing ‘juxtapositions’ of public space, private-ownership and a visual haptic that assumes the role of the “flaneur... who observes the street by taking part in it.” (Hamilton 110) The works that I have included in this piece are by no means a totalizing gesture. Instead, as subjective sketches based on a particular experience in a particular place and time, these are my attempts to graphically render urban scenarios that reflect the “moments in this stream of daily life...producing ‘poems of the street.’” (MacOrlan, Ronis and MacOrlan in Hamilton 110). Michael Corrente is a graphic designer working in Las Vegas.